Tradução e adaptação transcultural do instrumento de avaliação de competências do farmacêutico "Global Competency Framework (GbCF)" para o português do Brasil - Cruz, Carla Francisca dos Santos (2015)
With the growing need to prepare pharmacy students for clinical practice and ensure the quality of care, evaluation comes to play a essential role in graduation. However, there are little validated instruments to assessment of pharmacist´s clinical competencies and essential components for effective patient education. On the above, the aim of the present study was Cross-cultural adaptation of the "Global Competency Framework (GbCF)", making it an assessment tool of pharmacist clinical skills for the Portuguese of Brazil. Therefore, a systematic review was conducted to determine how the clinical competencies of pharmacists and/or pharmacy students are conceptualized and measured. A review was conducted into the databases, Scopus, Lilacs, Eric, and PubMed. With the keywords: "Clinical competence", "Pharmaceutical Care" and Pharmaceutical Education". The literature search identified 2,979 articles. After the exclusion process, 60 studies met the inclusion criteria. A total of 30 studies (50%) focused on general clinical skills, while the others examined specific clinical skills. Seventeen studies (28.3%) used the Objective Structured Clinical Examination (OSCE) as the method of clinical competence assessment. The instruments used in the studies varied greatly, with only eight studies (13.3%) using the same assessment instrument, which was the General Level Framework (GLF). This review concluded that there is a need for a validated assessment instrument to ensure that pharmacists´ competencies are globally applicable, transferable, accessible, and transparent. In addition, the cultural translation process GbCF instrument for Brazil started with the stages of translation and back translation. These were satisfactory to comply conceptual requirements, considering the linguistic aspects and the meaning of the content in the Brazilian reality. The combination of techniques Delphi and nominal group were employed to obtain a consensus on the items of the instrument is the most important aspects to be used in the evaluation of clinical skills of pharmacists. At this stage the judges proposed the modification of 65 items, including 41 textual changes, 22 exclusions, two groups and three reallocations of items in the four basic groups of skills that the instrument is divided. Version 3 generated was evaluated for semantic and idiomatic equivalence by the Judges Committee "A" formed by experts of this theme. The result showed that 31% of the items showed less than 80% agreement between judges and suffered semantic changes. Version 4 of the instrument was submitted to the cultural and conceptual equivalence by the expert committee "C" formed by experts of this theme, natives and / or residents of each of the five regions. According to the evaluation of this committee, there was need for modification of 29 items. The results showed concordance less than 80% to 80.60% of the items. The procedure resulted in the Portuguese version of the instrument entitled: General guidelines for assessment of pharmacist´s clinical competencies.